Designing Diana: Female Sports Entrepreneurs and Equestrian Innovation. Issue 7 (24th May 2018) - Munkwitz, Erica
Abstract: Throughout the late nineteenth century, many women turned their talents to improving horse sports as authors, equipment inventors, clothing designers, and trainers. Although these were male-dominated domains, many women quickly realized that there was a demand for their expertise and innovation as men did not ride side-saddle nor understand it. Thus, women became writers of sporting manuals (non-fiction) and sporting novels (fiction), which aided other women in improving and understanding riding and hunting. They also made significant innovations in equipment construction, such as saddles and stirrups, and clothing design, in fashioning specialized sporting garments. Finally, they also became riding instructors, training other women to ride and hunt well. Though some women forged ahead for their own benefit, seeking profit out of writing or teaching, there were also many other women who pursued new ideas to improve horse sports as a whole and encourage greater, safer, and better participation for other women. In these ways, female equestrians consciously acted as sporting entrepreneurs and are significant but underappreciated agents of change not only for equestrianism but for larger social, sartorial, and sporting transformations.